2018
DOI: 10.14406/acu.2018.020
|View full text |Cite|
|
Sign up to set email alerts
|

Patient's Perception for Developing Research Questions of a Clinical Practice Guideline of Korean Medicine for Degenerative Lumbar Spinal Stenosis: A Descriptive Cross-Sectional Survey

Abstract: The purpose of this study is to explore patients' perceptions that deserve attention when designing core questions for a clinical practice guideline of Korean medicine(KM) for degenerative lumbar spinal stenosis (LSS). Methods : Patients who had been admitted to Pusan National Korean Medicine Hospital from November 1, 2015 to October 31, 2016 were invited to the survey. Patients were eligible if they were both clinically and radiologically confirmed as degenerative LSS. The structured questionnaire was distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The needles were 27 gauge × 40 mm, and 27 gauge × 60 mm, and the thread length was 50 mm and 90 mm, respectively. Among the core muscle groups supporting the lumbar spine and pelvis, treatment was mainly applied to the painful side to reduce pain and scoliosis by strengthening the muscles [10][11][12][13][14]. Treatment was also performed on the other side of the lumbar spine and pelvis muscles to balance the muscle of the entire lumbar spine [14] (Fig.…”
Section: Teamentioning
confidence: 99%
“…The needles were 27 gauge × 40 mm, and 27 gauge × 60 mm, and the thread length was 50 mm and 90 mm, respectively. Among the core muscle groups supporting the lumbar spine and pelvis, treatment was mainly applied to the painful side to reduce pain and scoliosis by strengthening the muscles [10][11][12][13][14]. Treatment was also performed on the other side of the lumbar spine and pelvis muscles to balance the muscle of the entire lumbar spine [14] (Fig.…”
Section: Teamentioning
confidence: 99%
“…The typical symptoms of LSS include lower back pain, pain in the buttocks or legs when walking, and pain that worsens when leaning or bending backward [2,3]. A systemic review reported that the prevalence of LSS would be approximately 11% in the general population [4], and similar prevalence levels were also reported in Europe and the United States (U.S.) [4,5] While the prevalence of LSS in Korea has not been accurately estimated [6], a population-based cohort study in Japan reported that symptomatic LSS was present in approximately 10% of people with an increasing trend depending on age [7].…”
Section: Introductionmentioning
confidence: 99%